Accurate determination of vitamin B12 in infant formula by liquid chromatography/isotope dilution high-resolution mass spectrometry. (15th December 2022) - Wang, Xuxin; Li, Xiaomin; Liu, Xuehui; Zhao, Xiaotong; Li, Xiuqin; Zhang, Qinghe; Yin, Xiong
Abstract: Accurate determination of vitamin B12 (VB12 ) in food matrices remains a big challenge due to the instability of VB12 and extreme complexity of the various matrices. Both the matrix effect and recovery are the main parameters, which are needed to be evaluated meticulously in the measurement. An ultra-high performance liquid chromatography coupled to quadrupole Q-Exactive Plus orbitrap mass spectrometry (UHPLC-QE-Orbitrap-MS) has been developed to detect the VB12 in infant formulas. Besides, four calibration methodologies, including standard addition, standard addition-isotope dilution mass spectrometry, single point isotope dilution mass spectrometry (SP-IDMS), and standard calibration curve isotope dilution mass spectrometry were studied in detail to evaluate the accuracy and precision of the quantification values. The matrix effects of mass spectrometry could be compensated well via a facile SP-IDMS calibration method, which was validated by an F-test and the correction factor. UHPLC-QE-Orbitrap-MS with SP-IDMS calibration method could efficiently determine the VB12 in different infant formula matrices obtained from the supermarket. The precision with reproducibility less than 2.83%, and accuracy with a spiked recovery larger than 97.4% were obtained. The detection and quantification limits of the method were 0.05 and 0.20 μg/kg, respectively. Highlights: Accurate determination of vitamin B12 in complicated matrices is highly desirable. Four calibration methods have been developed to determine the vitamin B12 . Isotope dilution mass spectrometry could compensate the matrix effect well. UHPLC-ID-HRMS realized the accurate detection of the vitamin B12 in infant formula.